Pathological features and prenatal diagnosis in the newly recognised limb/pelvis-hypoplasia/aplasia syndrome. Issue 10 (October 1988) - Raas-Rothschild, A; Goodman, R M; Meyer, S; Katznelson, M B; Winter, S T; Gross, E; Tamarkin, M; Ben-Ami, T; Nebel, L; Mashiach, S
Abstract : A second family with the autosomal recessive disorder now referred to as the limb/pelvis-hypoplasia/aplasia syndrome is reported. It is speculated that the gene for this rare skeletal dysplasia may be confined to the Middle East gene pool. The disorder has been shown to be diagnosable prenatally in a pregnancy at risk by using ultrasonography.